Errors of Verbal Episodic Memory in Schizophrenia Patients and in Non-Clinical Group with Different Profiles of Schizotypal Traits - M.V. Alfimova; V.V. Plakunova; V.E. Golimbet (Клиническая и специальная психология, 2022)
The aim of the study was to provide a fine grain analysis of errors generated on word list learning tasks by schizophrenia patients and healthy controls with different profiles of schizotypal traits, since it can shed light on the cognitive mechanisms of memory impairment in these cohorts. 511 patients (mean age 33.40±11.53 years; 57% women) and 307 healthy controls (mean age 25.20±7.64 years; 73% women) completed the Rey Auditory Verbal Learning Test (A. Rey, 1964). The healthy subjects were assigned to groups with low, high, positive and negative schizotypy based on the Schizotypal Personality Questionnaire adapted by A.G. Efremov and S.N. Enikolopov (2002). In patients, symptomatology was assessed with the Positive and Negative Syndrome Scale adapted by S.N. Mosolov (2001). We analyzed the number of extra-list intrusions, their perseverations, frequency and strength of the associations with stimuli, as well as phonetic intrusions, intrusions from interference trails, and false recognition of semantic and phonetic lures. The results showed that patients are characterized by an increase in the number of extra-list intrusions and their perseverations, proactive interference and recognition of semantic lures; similar trends regarding extra-list intrusions and false recognitions were observed in the high schizotypy group. The data can be interpreted in favor of the idea of impairment of reality monitoring and insufficient encoding of stimulus’s surface features as inherent deficits of information processing in schizophrenia.